(untitled) (Fiep Bulletin - online, 2014)
Since 1979 the OMS recommends the acupuncture as efficient therapeutically resource, in special for analgesic. With the increment of the technological possibilities the association of electric stimulation through the needles was introduced to this so old technique: the electric acupuncture. Still today it has a lack in the standardization of procedures how much to the physical parameters that would have to be practiced in the electric acupuncture devices. This study of profile of bibliographical revision it has as objective to compile given on band of used electric frequency in electric acupuncture for analgesic effect, verifying which the searched and recommended frequencies. Research with resources biochemists, made in rats, for diverse authors, enters the years of 1979 the 2006, was observed that the bands of searched frequencies more in electric acupuncture are 2, 4 and 100 Hz, with set free endogenous corresponding evaluation of opioids. The data that more are happened again or coincided are the endorphins release of â in 2 Hz and dinorphins in 100 Hz. Some authors suggest in its research to associate in alternating way the use of low frequencies of 2 Hz and 100 high frequency of Hz, in one same session. In research with human beings, he observes yourself that the band of tested frequencies higher and is extended for top varying of 1 the 1000 Hz. One gives credit that these differences in the choice of the bands of frequencies in the research if must the proper characteristics of each author. These characteristics can vary in the available devices in the market until the adopted methodology to evaluate the improvement of the analgesic effect. Studies with human beings, as well as in other bands of frequency can be useful for the scientific progress of the electric acupuncture.